Implementasi Produk Investasi Sukuk Ritel SR 017 Pada Bank Syariah Indonesia KCP Rungkut 1 Surabaya - Danisa Nanda Pratiwi; Arin Setiyowati; Ainol Yaqin SM; Rizka Firdausy Nuzula (Universitas Muhammadiyah Ponorogo, 2023)
Retail Sukuk and Savings Sukuk are relevant funding alternatives used to raise funds from the public with low risk. Another advantage of Retail Sukuk and Savings Sukuk is that these investment products are specifically for Indonesian Citizens, thereby reducing Indonesia's dependence on foreign loans and reducing the risk of fluctuations in foreign exchange. This study uses a qualitative research method with a case study approach. The data sources used in this study are primary data sources through observation, interviews and documentation. Meanwhile, secondary data was obtained from a literature review related to the theme of retail sukuk and others. The data validity technique used in this study was triangulation of data sources. Data analysis techniques start from the process of collecting data, then compiling, categorizing data, looking for themes so that they can be interpreted. So that from this study the results of the analysis of retail sukuk SR 017 at BSI KC Rungkut 1 Surabaya, that the benefits of retail sukuk, investment guaranteed by the state (Safe), a period that fits the needs of financial planning, help build the country, halal, profitable and tax lower (10%), and affordable, with only IDR 1 million you can already invest in retail sukuk. And every risk in retail sukuk every year, has liquidity risk mitigation to overcome it. Retail Sukuk can be traded on the secondary market after three coupon payments. Retail Sukuk at BSI is in accordance with the legal basis stated in the fatwa of the National Sharia Council, so that it is in accordance with the background ofÂ Bank BSI which runs according to Islamic sharia.Â